Strategi Guru Dalam Sistem Pembelajaran Daring Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Negeri Kota Bengkulu - Suhaya, Noma; Ansyah, Edi; Hidayani, Masrifah (GHAITSA : Islamic Education Journal, 2021)
The purpose of this study was to find out the strategies of Islamic Religious Education teachers when teaching with an online system, the obstacles faced by Islamic Religious Education teachers when the online system, and the efforts of Islamic Religious Education teachers in dealing with problems when the online learning system in Bengkulu City Junior High School (SMP Negeri 7 , SMP Negeri 14, and SMP Negeri 6 Bengkulu city). The type of research used is qualitative research with descriptive qualitative approach. Data collection techniques in the form of interviews, observation, documentation. Research respondents were Islamic Religious Education teachers at SMP Negeri 7 Bengkulu City 2 people, SMP Negeri 14 Bengkulu City 1 people, and SMP Negeri 6 Bengkulu City 2 people. Based on the results of the study, it can be concluded that the teacher's strategy in the online learning system in Islamic religious education subjects at the Bengkulu City State Junior High School is that the teacher uses an online system learning strategy using Whatsapp, Yotube, Classroom, and Zoom application media. The obstacles faced by teachers when the online learning system was difficult to control students during learning, students did not understand the learning material, the collection of assignments was not structured, there were some students who did not have mobile phones, and there were some teachers who did not understand online applications such as Classroom and Zoom. Even though online learning is less effective to use, PAI teachers have tried their best so that learning can run effectively, some of the efforts of PAI teachers include collaborating with homeroom teachers and homeroom teachers so that students can always be supervised and really learn well, allow students to come to school once a week for those who do not have mobile phones, this is done so that students continue to follow PAI learning even though they are constrained by cellphones, and teachers help each other in using online applications.